Identifikasi Bakteri Kontaminan Pada Kultur Jaringan Bambu Jenis Fargesia scabrida - Erna Wulandari (Integrated Lab Journal, 2022)
Contaminant microbes are a common problem in plant tissue culture. Bacteria is a type of microbial that becomes a contaminant in plant tissue culture. This study aims to isolate and determine the diversity of bacterial contaminants of Fargesia scabrida bamboo tissue culture. In this study, bacterial isolation, phenotypic characterization included morphology, physiological tests, biochemical tests, identification, and phenetic numerical analysis were carried out. The results of this study indicated that 7 bacterial isolates were obtained. Based on profile matching using Bergey's Manual of Determinative Bacteriology, 1 isolate belongs to the genus Bacillus, 1 isolate belongs to Listeria, 2 isolates Erwinia, 2 isolates Lactobacillus, and 1 isolate belongs to the genus Klebsiella. The dendogram generated from the Simple Matching coefficient (SSM) parameter using the average linkage algorithm shows that at a similarity value of 70%, it is divided into 5 clusters. While the dendrogram generated from the SJ parameters using the average linkage/UPGMA at a similarity value of 70% 7 OTUs are divided into 7 clusters.